Predictors and Persistence of New Onset Clinical Remission in Rheumatoid Arthritis Patients - Navarro-Millán, Iris Y (2013)
OBJECTIVE: To determine the prevalence and persistence of new onset clinical remission in rheumatoid arthritis (RA) patients. METHODS: The Consortium of Rheumatology Researchers of North America (CORRONA) cohort was used to examine the prevalence of remission and associated comorbidities and RA therapies according to the 2011 American College of Rheumatology (ACR)/European League Against Rheumatism (EULAR) remission criteria. Factors influencing the likelihood of remaining in remission were identified by logistic regression with generalized estimating equations. Analysis of variance and Tukey’s test were used to determine differences in disability according to whether RA patients had been in remission or only low disease activity (LDA). RESULTS: A total of 2,105 individuals met ACR/EULAR remission criteria at the most recent visit within CORRONA, yielding an 8% point prevalence of remission. Patients with certain comorbidities (e.g. heart failure) were significantly less likely to achieve or remain in remission compared to those without these conditions (p<0.001 for each). Among prednisone users, the prevalence of remission was 1%–6% (depending on dose), compared to those not on prednisone (10%). More than 50% of patients who had consistently been in remission for ≥ 1 year were able to remain in remission over the next year. Patients consistently in remission had less disability than patients who achieved LDA or who fluctuated between remission and LDA. CONCLUSION: Patients consistently in remission for at least one year had a high likelihood to remain in remission. These individuals might be considered the most likely candidates for de-escalation or withdrawal of RA treatments.